2019
DOI: 10.1021/acs.langmuir.9b01925
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ligand Clusters on Multimodal Chromatographic Surfaces

Abstract: Multimodal chromatography is a powerful tool which uses multiple modes of interaction, such as charge and hydrophobicity, to purify protein-based therapeutics. In this work, we performed molecular dynamics simulations of a series of multimodal cation-exchange ligands immobilized on a hydrophilic self-assembled monolayer surface at the commercially relevant surface density (1 ligand/nm2). We found that ligands that were flexible and terminated in a hydrophobic group had a propensity to aggregate on the surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 43 publications
1
26
1
Order By: Relevance
“…Position restraint process was used in NVT and NPT ensemble steps. In addition, other algorithms such as Lennard-Jones potentials (Bilodeau et al, 2019) and PME (Collier et al, 2009) were employed to handle van der Waals and electrostatic interactions. The structures obtained at this stage were used to perform the desired analyzes.…”
Section: Discussionmentioning
confidence: 99%
“…Position restraint process was used in NVT and NPT ensemble steps. In addition, other algorithms such as Lennard-Jones potentials (Bilodeau et al, 2019) and PME (Collier et al, 2009) were employed to handle van der Waals and electrostatic interactions. The structures obtained at this stage were used to perform the desired analyzes.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand density has been shown to have an important impact on the behavior of MM chromatographic systems. ,, Further, recent simulation work in our group has shown that the Capto ligand at sufficiently high-ligand surface densities tends to self-associate, resulting in the formation of hydrophobic clusters on the surface . Importantly, this behavior did not occur in simulations at lower “Capto ligand” densities or with “Nuvia ligand”-functionalized surfaces.…”
Section: Results and Discussionmentioning
confidence: 86%
“…Finally, we employ MD simulations to provide further insights into the adsorption of the F C molecule in these different MM systems. MM ligand-immobilized SAM surfaces have been shown to present patterned surfaces with patches of charge and hydrophobicity in the absence of a protein . Here, we examine the impact of this ligand self-association phenomenon on protein adsorption by examining the intermolecular interactions and mechanisms occurring during binding of the F C to these different MM ligand surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…At pH 7.0 (Figure 3b), this orthogonality was apparent for both resins, while at pH 6.0 (Figure 3a), only Capto MMC ImpRes displayed this behavior. This difference in pH behavior is likely due to ligand density effects and perhaps ligand clustering (Bilodeau, Lau, et al, 2020;Bilodeau et al, 2019). These surprising results further demonstrate the importance of having a quantitative method to determine orthogonality which can identify counterintuitive orthogonality trends and opportunities.…”
Section: Analyzing Orthogonality Within Expression Systemsmentioning
confidence: 90%